(untitled) (The Macau Ricci Institute Journal, 2020)
Issued one year after the end of World War I, the apostolic letter of Pope Benedict XV Maximum Illud attempted to renew the Catholic church’s commitment to its mission. Highlighting the universality of Christian mission and fostering a new attention to the richness of cultures, the letter places itself at the starting point of the concept of inculturation. This new theological understanding deals with the awareness that the Spirit of God operates in the heart of men and cultures even before the arrival of the Gospel. It has found an astonishing fulfilment, one hundred years later, in the signing of a Document on Human Fraternity for World Peace and Living Together by Pope Francis and the Grand Imam of Al-Azhar Ahmad Al-Tayyeb that demonstrates a new approach not only toward interreligious dialogue, but also toward a new frontier of shared truths that, beyond religious differences, affirm our common commitment to human dignity, peace and mutual respect, reciprocity and care. The study suggests that this theological shift has been partially developed thanks to the spiritual experience of some of the protagonists of the Chinese “missionary laboratory” in the first decades of XX century, i.e. the two Lazarist priests Cotta andLebbe and, above all, Cardinal Celso Costantini.